2019
DOI: 10.1177/1758835918818335
|View full text |Cite
|
Sign up to set email alerts
|

Academic oncology clinicians’ understanding of biosimilars and information needed before prescribing

Abstract: Background:With increasing numbers of oncology biosimilars in the approval pipeline, it is important to investigate oncology clinicians’ understanding of biosimilars and what information they need prior to adoption.Methods:Between January and May 2018, 77 oncology clinicians (52 physicians, 16 pharmacists, and 9 advanced practice providers) completed a survey covering three domains: clinician understanding, prescription preferences, and patient involvement. An in-depth interview was designed based on themes id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 18 publications
4
40
1
Order By: Relevance
“…After screening for eligibility, we included 16 studies in the analysis ( Table 2 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The included studies were from Europe, UK, United States, Australia, Asia, and Africa [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The targeted healthcare professionals were: clinicians, GPs, pharmacists, nurses, consultants, care managers, and specialists in clinical settings where biologics are more involved such as oncology, rheumatology, endocrinology, gastroenterology, dermatology, nephrology, and hematology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening for eligibility, we included 16 studies in the analysis ( Table 2 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The included studies were from Europe, UK, United States, Australia, Asia, and Africa [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The targeted healthcare professionals were: clinicians, GPs, pharmacists, nurses, consultants, care managers, and specialists in clinical settings where biologics are more involved such as oncology, rheumatology, endocrinology, gastroenterology, dermatology, nephrology, and hematology.…”
Section: Resultsmentioning
confidence: 99%
“…Cook et al reported that 74% of academic oncology clinicians did not know the basic definition of biosimilars and 40.3% of them considered biosimilars and generics as the same molecules [ 30 ]. In Park et al’s survey, 66.2% of Asian gastroenterologists knew the basic concepts of biosimilars, but only 6% of them felt confident to use biosimilar monoclonal antibodies [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Indeed, before the actual prescribing of biosimilars, it is of utmost importance to know the efficacy, safety, cost, stability and appropriateness of biosimilars. [3][4][5] On the other hand, around 52.4% of the studied physicians believed that information regarding the acquisition of cost-differences is important to consider while using biosimilars. This study results were similar to another study which reported that around 86% of the participants were in favor of acquiring more information regarding cost differences between the reference drugs and biosimilars.…”
Section: Discussionmentioning
confidence: 99%
“…Biosimilars are quite effective among patients with chronic and severe diseases and in those patients who have failed to respond to earlier medications. 5,6 European Medicines Agency (EMA) stated that the biosimilarity profile of biosimilars in terms of efficacy and safety were quite high when compared with their therapeutic drugs. On the other side, a few healthcare organizations (HCOs) believed that biosimilars were complex proteins and could never be identical similar of the therapeutics agents.…”
Section: Introductionmentioning
confidence: 99%